ANALISIS MAHAR DALAM AKAD NIKAH - Siregar, Neila Hifzhi (IAIN Padangsidimpuan, 2019)
The history of dowry since the Prophet Syu'aib provided opportunities for workers for eight to ten years. The dowry process since hosting, may not be determined but implicitly there must be dowry if there is already a qobul permit, it may also be determined before the marriage contract. The amount of dowry is in accordance with the ability of the prospective husband. The legal basis comes from the Qur'an and hadith. Mahar is a condition for marriage not to get married. Terms of a worship are carried out before practicing the pillars of marriage. If the condition has finished the problem, just leave the gift after the initial intercourse between husband and wife. If it is stated that the number of dowry is proud of itself if there is a large number If there is a slight sense of humiliation, especially the wife and family and the husband. As if the rich bought valuable items if they were called the price. Mentioning wrong giving, even hurting the juice is certainly getting wrong. Mention dowry or alms to describe the alms of charity, not to believe in Allah and later in the day. Mahar is paid by the husband after the first initial contact